Growth, length-weight relationship, and condition factor of NIFI (Oreochromis sp.) and Srikandi Tilapia (Oreochromis aureus x niloticus) at the grow-out stage in the high salinity brackishwater ponds - Bambang Gunadi; Priadi Setyawan; Adam Robisalmi (Jurnal Iktiologi Indonesia, 2021)
Tilapia strain of NIFI (Oreochromis sp.) and Srikandi (Oreochromis aureus x niloticus) are superior strain of tilapia that able to grow well in brackish water ponds. However, an increasing water salinity might have an impact on a series adaptation process on fish that leads to various morphological changes. This study aimed to analyze the growth and length-weight relationship of both tilapia strain in brackishwater pond with salinity of 25-30 ppt. Research was conducted in brackishwater pond in Losari, Brebes Regency. Fish were reared in 5x5x1 m3 hapas installed in the pond for four months. At the end of experiment period, body length and weight measurement were carried out for 26 males and 34 females of NIFI strain and 31 males and 28 females of Srikandi strain. The result showed that the highest growth rate was shown by Srikandi strain and the highest length was shown by NIFI. Positive allometric growth was found in the Srikandi females, while Srikandi males as well as NIFI tilapia males and females showed a negative allometric growth. Length-weight relationship on males and females of NIFI strain followed the formula of W = 0.0583L2,632 and W = 0.0452L2,665, respectively. Whereas, on males and females of Srikandi strain followed the formula of W = 0.0358L2,8545 and W = 0.0287L3,1580, respectively. There was a strong correlation between length and weight of fish from both strains with the R2 value ranged between 0.80 – 0.87. Condition factor of males and females of NIFI were 1.853 and 2.009, while Srikandi tilapia males and females were 2.308 and 2.665, respectively. Red NIFI and Srikandi tilapia are able to adapt in a high salinity level of brackish water pond. Abstrak Ikan nila NIFI (Oreochromis sp.) dan ikan nila Srikandi (Oreochromis aureus x niloticus) merupakan strain ikan nila unggul yang dapat dibudidayakan di perairan tambak air payau. Salinitas tinggi akan berdampak pada serangkaian proses adaptasi yang dapat memicu perubahan morfologis ikan. Penelitian bertujuan untuk menganalisis pertumbuhan, hubungan panjang-bobot, dan faktor kondisi kedua strain pada tambak bersalinitas 25-30 ppt. Kegiatan penelitian dilakukan di tambak Losari, Kabupaten Brebes. Ikan dipelihara di tambak dengan menggunakan waring berukuran 5x5x1 m3 selama empat bulan. Pada akhir pemeliharaan sampel sebanyak 26 jantan dan 34 betina ikan nila NIFI serta 31 jantan dan 28 betina ikan nila Srikandi diambil dan dilakukan pengukuran panjang dan bobot. Hasil penelitian menunjukkan bahwa pertumbuhan bobot tertinggi ditunjukkan ikan nila Srikandi dan pertumbuhan panjang tertinggi ditunjukkan ikan nila NIFI. Pola pertumbuhan alometrik positif ditemukan pada Srikandi betina, sedangkan pada Srikandi jantan, serta nila NIFI jantan dan betina menunjukkan pertumbuhan alometrik negatif. Hubungan panjang-bobot ikan nila NIFI jantan dan betina mengikut persamaan W = 0,0583L2,632 dan W = 0,0452L2,665, pada ikan nila Srikandi jantan dan betina mengikuti persamaan W = 0,0358L2,8545 dan W = 0,0287L3,1580. Terdapat korelasi erat antara panjang dan bobot ikan kedua strain dengan nilai R2 antara 0.80 - 0.87. Nilai faktor kondisi nila NIFI jantan dan betina adalah 1,853 dan 2,009, serta pada nila Srikandi jantan dan betina adalah 2,308 dan 2,665. Ikan nila NIFI dan Srikandi mampu beradaptasi dengan baik pada perairan tambak bersalinitas tinggi.